2015
DOI: 10.1103/physrevlett.114.256801
|View full text |Cite
|
Sign up to set email alerts
|

Strain Doping: Reversible Single-Axis Control of a Complex Oxide Lattice via Helium Implantation

Abstract: We report on the use of helium ion implantation to independently control the out-of-plane lattice constant in epitaxial La 0.7 Sr 0.3 MnO 3 thin films without changing the in-plane lattice constants. The process is reversible by a vacuum anneal. Resistance and magnetization measurements show that even a small increase in the out-of-plane lattice constant of less than 1% can shift the metal-insulator transition and Curie temperatures by more than 100°C. Unlike conventional epitaxy-based strain tuning methods wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(108 citation statements)
references
References 42 publications
(68 reference statements)
5
101
2
Order By: Relevance
“…A recent study also simulated the bond angle-dependent magnetism of LaMnO 3 ultrathin films sandwiched in SrTiO 3 layers, which gave a successful explanation of experimental observation (36). The conventional coefficients are adopted according to previous studies to give a proper description to La 1-x Sr x MnO 3 (36,70,71). Then, the effects of Mn-O-Mn bending bonds to both the double exchange and .…”
Section: Methodsmentioning
confidence: 99%
“…A recent study also simulated the bond angle-dependent magnetism of LaMnO 3 ultrathin films sandwiched in SrTiO 3 layers, which gave a successful explanation of experimental observation (36). The conventional coefficients are adopted according to previous studies to give a proper description to La 1-x Sr x MnO 3 (36,70,71). Then, the effects of Mn-O-Mn bending bonds to both the double exchange and .…”
Section: Methodsmentioning
confidence: 99%
“…In the bulk, Morozovska 382 analyzed the case of Vegard strain changing the sign of the first term in the Landau expansion, resulting in a ferroelectric phase transition. Recently, the attempt to control such states via He atom implantation was made by Ward et al, who demonstrated that such strain control modulates the metal-insulator transition in La0.7Sr0.3MnO3 383 , and can also tune the structure of SrRuO3 films between orthorhombic and tetragonal phases. 384 Finally, an extremely broad range of emergent behaviors can be anticipated due to coupling between surface electrochemistry and bulk ferroelectricity.…”
Section: Phenomenamentioning
confidence: 99%
“…He implantation is a random process where the final He concentration typically follows a roughly Gaussian distribution. For He ions at 4 keV the center of this Gauss curve is at about 40 nm and the width is approximately 30nm [13]. That means that in order to achieve a roughly homogeneous He distribution, and thus strain state, across the film the thickness should not exceed 25nm.…”
Section: Structural Characterizationmentioning
confidence: 99%